(3GdefJNH ef cJGH GdeMGRGI hGdeLGRGIs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s
(3ChdgG (B:s
"(3aEf GdebQ GdCTQa CHG GdMSf Ydi Hf aVd Gddg UGMH OjhGf GdEfTGA GdTQja HGdCHhGH GdZGdjI deG hbaJ HGdOjGQ GdeUQjI GdeMQhSI EdN s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs